Studying the role of cadherin-11 as a novel biomarker of kidney fibrosis - Saeed Abdelwahab; Hayam Aref; Manal Salman; Abdelrahman Khedr; Ghada Gaafar; Abdelrahman Elbraky (Journal of Nephropathology, 2024)
Introduction: Kidney fibrosis is the ultimate common pathway observed in all chronic nephropathies, which arises due to the pathological accumulation of extracellular matrix (ECM) components in response to persistent injury. While biopsy is widely regarded as the preferred diagnostic method, it is an invasive procedure with inherent limitations. Alternatively, cadherin-11 (CDH-11) serves as an exceptional noninvasive biomarker for kidney fibrosis. Objectives: To measure serum CDH-11 among patients indicated for native kidney biopsy. In addition, this study aimed to examine the correlation between CDH-11 levels and kidney biopsy’s interstitial fibrosis tubular atrophy (IFTA) score to investigate its sensitivity and specificity as a biomarker of kidney fibrosis. Patients and Methods: The current study adopted a cross-sectional design involving 100 clinically indicated patients for native kidney biopsy. All participants were subjected to serum CDH-11 measurement on the biopsy day. This study was carried out in Ain Shams University Hospitals. Results: The results indicated that the median value of CDH-11 was 3.9 ng/mL (2.2–7.6). This value was found to be significantly higher in cases with arteriosclerosis at a P value <0.001. It was highest in grade 3, followed by 2, then 1, then zero of all chronicity grading scale points (global and segmental, tubular atrophy, and interstitial fibrosis) at a P value <0.001. Consequently, it was highest in severe, followed by moderate, then mild, and lowest in minimal IFTA with (median of 12.0 (7.6–16.0), 6.1 (4.4–7.7), 3.5 (2.2–4.6), 1.2 (0.5–2.6), respectively. The area under the curve was 0.645, and the optimal cut-off level was ≥5.6 ng/dL (90.9% sensitivity and 71.8% specificity). Conclusion: Based on the current study findings, it can be determined that CDH-11 serves as a highly accurate and precise indicator in patients with kidney fibrosis. Furthermore, the level of CDH-11 can predict the degree of fibrosis across various etiologies of kidney disease.